2015
DOI: 10.1002/2014jd022229
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of beams of positrons, neutrons, and protons associated with terrestrial gamma ray flashes

Abstract: Positron beams have been observed by the Fermi satellite to be correlated with lightning leaders, and neutron emissions have been attributed to lightning and to laboratory sparks as well. Here we discuss the cross sections to be used for modeling these emissions, and we calculate the emissions of positrons, neutrons, and also protons from lightning leaders. Neutrons were first erroneously attributed to fusion reactions, but the photonuclear reaction responsible for neutrons should create protons as well. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 55 publications
3
74
0
Order By: Relevance
“…Various measurements have shown that electric fields in streamer discharges can reach field strengths of up to ≈10 E k (Kim et al, 2004; Pancheshnyi et al, 2000; Spyrou & Manassis, 1989) consistent with results of streamer simulations and analytic estimates (Chanrion & Neubert, 2008; Köhn et al, 2018; Liu & Pasko, 2004; Moss et al, 2006; Naidis, 2009; Qin & Pasko, 2014; Tholin & Bourdon, 2013). In the vicinity of lightning leader tips, calculations have shown that the enhanced electric field can exceed several times the breakdown field (Köhn, Diniz, Harakeh, 2017; Köhn & Ebert, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various measurements have shown that electric fields in streamer discharges can reach field strengths of up to ≈10 E k (Kim et al, 2004; Pancheshnyi et al, 2000; Spyrou & Manassis, 1989) consistent with results of streamer simulations and analytic estimates (Chanrion & Neubert, 2008; Köhn et al, 2018; Liu & Pasko, 2004; Moss et al, 2006; Naidis, 2009; Qin & Pasko, 2014; Tholin & Bourdon, 2013). In the vicinity of lightning leader tips, calculations have shown that the enhanced electric field can exceed several times the breakdown field (Köhn, Diniz, Harakeh, 2017; Köhn & Ebert, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…One is that seed electrons from cosmic ray ionization of the atmosphere are born with energies in the runaway regime and are further accelerated by the ambient electric field in a cloud, forming a relativistic runaway electron avalanche (RREA; Babich et al, 2012; Dwyer, 2003; Gurevich et al, 1992; Gurevich & Karashtin, 2013; Wilson, 1925) including the feedback mechanism where high‐energy electrons produce high‐energy gamma rays through the bremsstrahlung process which subsequently produces secondary electrons and positrons through photoionization, Compton scattering, or pair production (Dwyer, 2003, 2007; Kutsyk et al, 2011; Skeltved et al, 2014). The other is that thermal (cold) electrons are accelerated into the runaway regime in the high, but very localized, field of streamer tips as well as by the enhanced electric fields in the vicinity of lightning leader tips (Babich et al, 2015; Celestin & Pasko, 2011; Chanrion & Neubert, 2008; Köhn et al, 2014; Köhn & Ebert, 2015; Köhn, Diniz, Harakeh, 2017) and subsequently turn into relativistic RREAs (Carlson et al, 2010, 2006; Köhn, Diniz, Harakeh, 2017; Moss et al, 2006). In the following we explore the streamer mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, polarization often enhances direct ionization by positrons, so that they can be more penetrating and more ionizing than electrons, a result of potential import in analyses of astrophysical (e.g., [8]) and atmospheric events (e.g., [9]) as well as in positron-track simulations for dosimetry in positron emission tomography (e.g., [10]). In turn, these studies contribute to the motivation for investigating the interaction of e þ with water which accounts for about 60% of the human body and which is the most abundant greenhouse gas in the atmosphere.…”
mentioning
confidence: 99%
“…In this work, we explore whether multiple streamers combined with multiple head-on collisions can possibly accelerate the electrons (≥1 keV) produced by a single-streamer head-on collision (Ihaddadene & Celestin, 2015;Köhn et al, 2017) to the higher values (50-500 keV) observed in the experiments. Similar modeling approaches and different electric field configurations have been previously used to study runaway electron production (e.g., Köhn & Ebert, 2015;Kochkin, Köhn, et al, 2016;Kochkin, Lehtinen, et al, 2016). To test this hypothesis, we use a static distribution of multiple dielectric ellipsoids of different lengths and diameters equivalent in size to streamers we usually observe in laboratory experiments (see Figure 3) with peak and body electric fields reasonably close to streamer simulation results.…”
Section: Streamer-streamer Head-on Collisionmentioning
confidence: 83%